Effects of cis-Jasmone Treatment of Brassicas on Interactions With Myzus persicae Aphids and Their Parasitoid Diaeretiella rapae - Ali, Jamin; Covaci, Anca D.; Roberts, Joe M.; Sobhy, Islam S.; Kirk, William D. J.; Bruce, Toby J. A. (Frontiers in Plant Science, 2021)
There is a need to develop new ways of protecting plants against aphid attack. Here, we investigated the effect of a plant defence activator, cis-jasmone (CJ), in a range of cultivars of Brassica napus, Brassica rapa and Brassica oleracea. Plants were sprayed with cis-jasmone or blank formulation and then tested with peach potato aphids (Myzus persicae Sulzer) (Hemiptera: Aphididae) aphids and their parasitoid Diaeretiella rapae M’Intosh (Hymenoptera: Braconidae). CJ treated plants had significantly lower aphid settlement than control plants in a settlement bioassay. Conversely, in a foraging bioassay, D. rapae parasitoids spent a significantly longer time foraging on CJ treated plants. As CJ is highly volatile and would have evaporated before plants were tested, these effects are due to a switching effect CJ has on plant defence metabolism. Our results reveal that CJ treatment makes plants less attractive to and less suitable for M. persicae but more attractive to D. rapae in a range of brassica cultivars. It is likely that these effects are due to changes in volatile emission indicating activation of defence and presence of conspecific competitors to aphids but presence of prey to parasitoids. Increases in volatile emission were found in CJ induced plants but varied with genotype. These results build on earlier studies in Arabidopsis and show that tritrophic interactions are influenced by CJ in a wide range of brassica germplasm. The implication is that CJ is a promising treatment that could be used in brassica crops as part of an integrated pest management system.